2022
DOI: 10.1002/ange.202214977
|View full text |Cite
|
Sign up to set email alerts
|

Electrifying Adipic Acid Production: Copper‐Promoted Oxidation and C−C Cleavage of Cyclohexanol

Abstract: Adipic acid is a central platform molecule for the polymer industry. Production of adipic acid with electroreforming technology is more sustainable compared to the thermochemical synthesis route. We discovered that incorporation of Cu 2 + into a Ni hydroxide lattice significantly improved the electrocatalytic oxidation of cyclohexanol into adipate with a high yield (84 %) and selectivity (87 %). This Cu promotion effect serves as a mechanistic probe that can be combined with product analysis, steady-state kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The XPS fitting results of the Ni 2p high-resolution spectrum (Figure S4) showed that the signals of 855.06 and 872.66 eV belonged to the Ni 2+ peaks of Ni 2p 3/2 and Ni 2p 1/2 , respectively; 856.55 and 874.15 eV correspond to the Ni 3+ peaks of Ni 2p 3/2 and Ni 2p 1/2 , while the rest are satellite peaks. , After doping with Cu and Co, the peak area ratio of Ni 3+ /Ni 2+ increased significantly compared to that of Ni(OH) 2 (Table S1). In the XPS fine spectrum of Cu 2p (Figure c), CuCo–Ni(OH) 2 showed the Cu + and Cu 2+ metal peak signals at 932.05 and 934 eV for Cu 2p 3/2 . Compared to Cu–Ni(OH) 2 , the peak area ratio of Cu + in CuCo–Ni(OH) 2 was decreased, indicating that Cu and Co and Co jointly share the electron transfer from Ni.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS fitting results of the Ni 2p high-resolution spectrum (Figure S4) showed that the signals of 855.06 and 872.66 eV belonged to the Ni 2+ peaks of Ni 2p 3/2 and Ni 2p 1/2 , respectively; 856.55 and 874.15 eV correspond to the Ni 3+ peaks of Ni 2p 3/2 and Ni 2p 1/2 , while the rest are satellite peaks. , After doping with Cu and Co, the peak area ratio of Ni 3+ /Ni 2+ increased significantly compared to that of Ni(OH) 2 (Table S1). In the XPS fine spectrum of Cu 2p (Figure c), CuCo–Ni(OH) 2 showed the Cu + and Cu 2+ metal peak signals at 932.05 and 934 eV for Cu 2p 3/2 . Compared to Cu–Ni(OH) 2 , the peak area ratio of Cu + in CuCo–Ni(OH) 2 was decreased, indicating that Cu and Co and Co jointly share the electron transfer from Ni.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Wang et al attached triphenylphosphine oxide (TPPO) units to the TRZ acceptor to boost the electron‐transporting ability of the dendrimers 16 . As a result, the resultant dendrimers, CzTAZPO and sCzTAZPO, supported their devices with slow efficiency roll‐off and high EQEs of 12.6% and 9.1%, respectively.…”
Section: Recent Advances Of Tadf Dendrimersmentioning
confidence: 99%